The afterlife of Enlightened Absolutism: commemoration of Maria Theresa and Joseph II and the politics of liberal reform in nineteenth-century imperial Austria. Issue 2 (4th March 2019) - Aliprantis, Christos
ABSTRACT: This article sheds new light on the ways that the enlightened Habsburg rulers Maria Theresa and Joseph II were perceived in the Austrian political landscape of the 1860s, focusing on the liberal school reform bills of 1868 and 1869. In this period when State–Church relations emerged as a crucial political topic in Austria, the memory of Joseph II and his mother, who had first enforced state control over the Church as well as education, became a useful rhetorical instrument over policy legitimization. In the 1860s, the Austrian liberals claimed ideological continuity with Maria Theresa and Joseph II and used his name to attract historical depth in their aim of abolishing the Concordat of 1855, which had granted excessive legal and educational privileges to the Catholic Church. The advocates of the Concordat argued on the other hand that through this pact with the Vatican, the historic rights of the Church against state oppression -crystallized in the figure of Joseph II- were defended. Thorough analysis of how nineteenth-century Austrians perceived their past can be valuable both as a study on the aftermath of Enlightened Absolutism and, more importantly, in assisting to comprehend the worldview and motivation of the mid-century liberal politics in imperial Austria.